Active labour-market policies in Germany - Wapler, Rüdiger; Werner, Daniel; Wolf, Katja (Nürnberg, 2014)
"Active labour-market policy (ALMP) not only affects the labour-market success of participants. Due to indirect effects, they might also affect the job perspectives of non-participants. Hence, even if ALMP programmes have a positive effect for the participants, this does not mean that ALMP improves the labour-market situation as a whole. Therefore, this paper deals with the question whether ALMP improves the matching-process between job-seekers and vacancies and thus increases the total number of outflows from unemployment into employment at the regional level. To answer this question, we use data for local employment offices of the German Federal Employment Agency for the time period 2006 to 2010 and focus on job-seekers subject to unemployment insurance. As microeconometric evaluation studies show, the search effectiveness of programme participants is low during participation due to the lock-in effect, but ideally increases at the end of the programme. In contrast to previous studies on aggregate effects of ALMP, we take this into account and explicitly differentiate current and former programme participants. The result from our augmented matching function shows that the lock-in effect is also present on the regional level. However, a higher search effectiveness after completion of the programme is not outweighed by potential indirect effects on non-participants. A higher share of former programme participants among the job-seekers in a region leads to an increase of the regional matches. This findings show that the application of ALMP improves the regional matching process. However, this effect varies largely between different types of programmes. Positive effects occur for long-term vocational training and wage subsidies as well as for in-firm training measures. Further, our results show that the effect of the different programme types depends to some extent on the regional labour-market situation."